Ask a New Question
Search
Given f(x)=x^2+4 and g(x)=3x+1 simplify g^-1(x)(inverse)
please show work and explain
1 answer
g^-1(x) = (x-1)/3
solve for x and then swap names:
g=3x+1
3x = g-1
x = (g-1)/3
Ask a New Question
or
answer this question
.
Similar Questions
Solve using inverse operations. Use the sketch pad to show your work. If you prefer to show your work on paper, you can upload
1 answer
Solve using inverse operations. Use the sketch pad to show your work. If you prefer to show your work on paper, you can upload
1 answer
Find the inverse of the function below. Graph the function below and the inverse function. Determine the domain, range, and
2 answers
Find the inverses of the following functions.
y = 3(x - 1)^2, x >= 1 Work: x = 3(y - 1)^2 x = 3(y - 1)(y - 1) x = 3(y^2 - y - y +
1 answer
more similar questions